What constitutes an attractive education system for young people? A perspective from the Brazil-Italy dialogue (Revista Contexto & Educação, 2025)
This qualitative study is the result of the first phase of research by the researcher-author in the context of a postdoctoral internship in Italy in the second half of 2024. The main objective of this first manuscript was to investigate some differences and similarities regarding the organization of the pre-university education system in Brazil and Italy, in light of student expectations. The choice of the theme of the organization of the education system in both countries is the first comparative aspect and, hypothetically, can guide how attractive the academic universe is for the new generations. For this purpose, the following research question was structured: What is considered an attractive education system for young people who aim to enter the university system? What were their initial expectations and to what extent were they met in light of the needs presented by the current sociocultural context in which they live? The data for this research were produced through an initial exploratory phase in official documents, followed by a narrative phase (personal memory) of two participants, one Italian and the other Brazilian. As a result, the main stages that configure pre-university Basic School Education in Italy and Brazil according to official regulations were first presented. Then, according to Moraes and Galiazzi (2006), three categories emerged from the Discursive Textual Analysis of the narrative memories of the participants in this research, who recently completed their university studies. It was concluded that the reasons that guaranteed the “motivation” to continue studying belong to the sociocultural plane, in a dialectical relationship of the sociogenesis and ontogenesis dimensions, without disregarding the microgenesis of each participant.
Keywords: Motivation; sociocultural context; mediation